2015
DOI: 10.1038/srep17485
|View full text |Cite|
|
Sign up to set email alerts
|

A new sensitizer DVDMS combined with multiple focused ultrasound treatments: an effective antitumor strategy

Abstract: Sonodynamic therapy (SDT) was developed as a promising noninvasive approach. The present study investigated the antitumor effect of a new sensitizer (sinoporphyrin sodium, referred to as DVDMS) combined with multiple ultrasound treatments on sarcoma 180 both in vitro and in vivo. The combined treatment significantly suppressed cell viability, potentiated apoptosis, and markedly inhibited angiogenesis in vivo. In vivo, the tumor weight inhibition ratio reached 89.82% fifteen days after three sonication treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…8 SDT induces the generation of reactive oxygen species (ROS) and apoptosis in tumor cells, and has been shown to greatly improve the outcome of cancer patient by promoting tumor shrinkage while reducing metastases of tumor cells. 9, 10, 11, 12, 13 We previously revealed that SDT could effectively induce apoptosis of macrophage and macrophage foam cell via mitochondrial-caspase dependent pathway 14, 15 and rapidly stabilize atherosclerotic plaques. 16 Meanwhile, SDT possesses high repeatability owing to its relative security and accessibility.…”
mentioning
confidence: 99%
“…8 SDT induces the generation of reactive oxygen species (ROS) and apoptosis in tumor cells, and has been shown to greatly improve the outcome of cancer patient by promoting tumor shrinkage while reducing metastases of tumor cells. 9, 10, 11, 12, 13 We previously revealed that SDT could effectively induce apoptosis of macrophage and macrophage foam cell via mitochondrial-caspase dependent pathway 14, 15 and rapidly stabilize atherosclerotic plaques. 16 Meanwhile, SDT possesses high repeatability owing to its relative security and accessibility.…”
mentioning
confidence: 99%
“…All SDT studies are focused primarily on cancer treatment [19][20][21]. Previous studies demonstrated the sonodynamic effect of ALA on macrophages that are responsible for the progression of atherosclerosis [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…[14, 17] Yet, RB4 is not a photosensitive molecule. The photon theory of sonodynamic therapy might not be applicable in RB4.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reported sonosensitizers are also photosensitizers or derived from photosensitizers; therefore, the accepted mechanism of action of SDT is similar to that of PDT. [14, 17] Conversely, a few non-photosensitive sonosensitizers have also been identified. [1820] These sonosensitizers cannot be excited by light; but under insonation, reactive oxygen species (ROS) were generated, triggering apoptosis.…”
Section: Introductionmentioning
confidence: 99%